2019
DOI: 10.3892/ijo.2019.4678
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of MAF1�homolog, negative regulator of RNA polymerase�III in colorectal cancer progression

Abstract: Polymerase (Pol) III dependent transcription controls the abundance of transfer RNAs, 5S ribosomal RNA and small non coding RNAs within cells, and is known to serve an essential role in the maintenance of intracellular homeostasis. However, its contribution to cancer progression has not been extensively explored. The present study demonstrated that the evolutionarily conserved MAF1 homolog, negative regulator of RNA Pol III (MAF1) may be closely associated with malignant potential and poor prognosis in colorec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…Maf1 siRNA (5’-GGCUCAAGCGAAUCGUCUUTT-3’) and ATF5 siRNA (5’-GTCCAAATCATGAAATGTTTG-3’) published before [ 20 , 48 ]. For transient knockdown, cells were transfected with siRNA using siRNA-Mate transfection reagent (Genepharma) according to manufacturer’s instruction.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Maf1 siRNA (5’-GGCUCAAGCGAAUCGUCUUTT-3’) and ATF5 siRNA (5’-GTCCAAATCATGAAATGTTTG-3’) published before [ 20 , 48 ]. For transient knockdown, cells were transfected with siRNA using siRNA-Mate transfection reagent (Genepharma) according to manufacturer’s instruction.…”
Section: Methodsmentioning
confidence: 99%
“…Maf1 is an mTORC1 effector that has significant roles in cancer biology [ 20 24 ]. Maf1 is phosphorylated by mTORC1 at certain Serine and Threonine to regulate RNA Polymerase III-dependent transcription of tRNAs, microRNAs and other small nuclear RNAs [ 7 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“… 19 ASH2L 42 ARMC1 ARMC1, YTHDF3, TCEA1, UBE2W, IMPAD1, ARFGEF1, STAU2, RB1CC1, LYPLA1, VCPIP1, RAB2A 8q13.1 Neither Breast cancer 43 and thyroid cancer 44 YTHDF3 45 UTP23 UTP23, FAM91A1, RAD21, MTDH, TAF2, ATP6V1C1, AZIN1, OTUD6B, SLC25A32, VIRMA 8q24.11 Neither Breast cancer 43 , 46 and non-small cell lung cancer 47 RAD21 48 SHARPIN SHARPIN, CYHR1, HSF1, VPS28, BOP1, HGH1, EXOSC4, COMMD5, ZC3H3, DGAT1, ADCK5, MAF1, FBXL6, PUF60, SLC52A2, PPP1R16A, PYCR3, GPAA1, GLI4, LRRC14 8q24.3 Refs. 18 , 19 SHARPIN 49 , MAF1 50 YME1L1 YME1L1, KIF5B, WAC, ABI1, RAB18, ACBD5 10p12.1 Neither Diffuse Large B-Cell Lymphoma 51 RAB18 52 MED21 MED21, MRPS35, ERGIC2, INTS13, FGFR1OP2 12p11.23 Ref. 18 ERGIC2 53 CLTC CLTC, INTS2, MED13, APPBP2, BPTF, HELZ, DCAF7, CCDC47 17q23.1 Refs.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, our results showed that the regulation of transcription from the RNA polymerase II promoter may be associated with one of the most prominent differences in chemoresistance in CRC. Researchers have found that RNA polymerase could modulate drug resistance and cancer progression in CRC ( 45 , 46 ), but the specific mechanism of RNA polymerase II in chemoresistance should be explored in the future. The PI3K-Akt signaling and MAPK signaling pathways are important in the maintenance of cancer stem cells, which can mediate therapy resistance by dormancy, increased DNA repair, drug efflux, and so on ( 21 ).…”
Section: Discussionmentioning
confidence: 99%